Galactorrhea in infant induced by maternal antidepressants use: case report - Gomes, Érica Batalha; Nogueira, Camila Távora; Gomes, Arthur Lopes da Silva; Oliveira , Aline de Albuquerque; Guimarães, Mara Rocha Crisóstomo; Belchior, Heloísa Oliveira Magalhães; Guimarães, Tiago Moraes (Brazilian Journal of Case Reports, 2023)
Breastfeeding is essential in nutrition, newborn development and for the mother-baby bond. Evidence of increased depressive disorders and growing need for drug use in the postpartum period has made the use of antidepressants during lactation an important issue to be discussed. The infant presented a nipple lesion with phlogistic signs and galactorrhea. Initially, the diagnosis of infection secondary to excessive handling was suggested and antibiotic therapy was prescribed with the resolution of the condition. However, 2 more episodes occurred, and the patient was referred to a mastologist who raised the hypothesis of galactorrhea due to maternal antidepressant use. present study is notable for showing, for the first time in the literature, a case report of infant galactorrhea induced by maternal use of antidepressants. Although the chances of occurrence of this condition are low, due to the drugs’ safety profile and the reduced concentration of these substances on breastmilk, it is important to consider this hypothesis in the presence of recurrent milk production with no other plausible explanation.